2019
DOI: 10.1111/jvh.13095
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis evolution in chronic hepatitis B e antigen‐negative patients across a 10‐year interval

Abstract: Summary The degree of liver fibrosis in chronic hepatitis B (CHB) infection influences outcome and management. Existing data describing the long‐term dynamic changes of liver fibrosis are limited. This study aimed to evaluate the evolution of liver fibrosis in CHB across a 10‐year period. CHB patients with liver stiffness measurement (LSM) by transient elastography 10 years ago were recruited for follow‐up LSM. Fibrosis stages were classified according to EASL‐ALEH guidelines. Fibrosis progression/regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…In a parallel study of 361 patients with HBeAg‐negative CHB, 3% had ≥30% increase in LSM and 8% required anti‐viral therapy at a mean follow‐up of 44 months 43 . In a longer term study of 459 patients with HBeAg‐negative CHB, 9% had ≥1 stage of fibrosis progression as estimated by LSM and 51% required anti‐viral therapy in 10 years 44 . Therefore, performing fibrosis assessment in untreated patients at an interval of 3 years or more is reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel study of 361 patients with HBeAg‐negative CHB, 3% had ≥30% increase in LSM and 8% required anti‐viral therapy at a mean follow‐up of 44 months 43 . In a longer term study of 459 patients with HBeAg‐negative CHB, 9% had ≥1 stage of fibrosis progression as estimated by LSM and 51% required anti‐viral therapy in 10 years 44 . Therefore, performing fibrosis assessment in untreated patients at an interval of 3 years or more is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…required anti-viral therapy in 10 years. 44 24,[43][44][45][46] Therefore, the practical role of HCC risk scores is limited in identifying patients who may benefit from but are not indicated for treatment by current practice guidelines (Figure 1). practice guidelines and reimbursement policies recommend using HCC risk scores in deciding treatment initiation in patients with CHB.…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…Recently, a cohort study evaluated the evolution of liver fibrosis using liver stiffness measurement, along with hepatic steatosis by controlled attenuation parameter, in 459 HBeAgnegative patients across a 10-year interval. 112 They found that hepatic steatosis was associated with fibrosis progression in CHB patients (OR = 7.799). 112 Following similar measurement methods, their prior cross-sectional study also showed a positive association between severe steatosis and severe fibrosis in both treatment-naïve patients (OR = 3.60) and patients receiving NAs treatment for at least three years (OR = 1.95).…”
Section: Aug Mented Ris K Of Fib Ros Is Cirrhos Is and H CC In Namentioning
confidence: 98%
“…112 They found that hepatic steatosis was associated with fibrosis progression in CHB patients (OR = 7.799). 112 Following similar measurement methods, their prior cross-sectional study also showed a positive association between severe steatosis and severe fibrosis in both treatment-naïve patients (OR = 3.60) and patients receiving NAs treatment for at least three years (OR = 1.95). 113 According to another study, among 1202 patients with CHB, the proportion of individuals with severe fibrosis was significantly higher among those with severe steatosis than those with mild or moderate steatosis (23.2% vs 12.6%).…”
Section: Aug Mented Ris K Of Fib Ros Is Cirrhos Is and H CC In Namentioning
confidence: 98%
See 1 more Smart Citation